2018
DOI: 10.1186/s12885-018-4901-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor size on survival of patients with resected pancreatic ductal adenocarcinoma: a systematic review and meta-analysis

Abstract: BackgroundThe impact of tumor size on prognosis for surgically treated patients with pancreatic ductal adenocarcinoma (PDAC) remains controversial. A systematic review and meta-analysis was performed to evaluate this issue.MethodsRelevant studies published from January 2000 to June 2017 were identified through EMBASE and PUBMED. Data were pooled for meta-analysis using Review Manager 5.3.ResultsTwenty eight observational studies involving a total of 23,945 patients were included. Tumors > 2 cm was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…A systematic review showed that with the exception of postsurgical blood transfusion, tumor characteristics (e.g., size, lymph node status, and differentiation) were the only features significantly associated with survival after pancreatic resection [ 9 ]. Particularly, PaC size > 2 cm was an independent factor associated with poor post-surgical prognosis [ 10 ], and this category has been incorporated in both the sixth/seventh and the eighth TNM staging systems [ 33 , 34 ]. Notably, neural invasion was also determined to be an independent prognostic factor in PaC [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed that with the exception of postsurgical blood transfusion, tumor characteristics (e.g., size, lymph node status, and differentiation) were the only features significantly associated with survival after pancreatic resection [ 9 ]. Particularly, PaC size > 2 cm was an independent factor associated with poor post-surgical prognosis [ 10 ], and this category has been incorporated in both the sixth/seventh and the eighth TNM staging systems [ 33 , 34 ]. Notably, neural invasion was also determined to be an independent prognostic factor in PaC [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A tumour of volume 1 cm 3 was predicted to correspond to a mean plasma clonal MAF of 0.008% [ 25 ]. This presents a direct challenge for the detection of ctDNA fragments released from PDAC lesions, which typically range from ≤2 cm to ∼5 cm in diameter [ 96 , 97 ]. The tumour microenvironment in PDAC can further impair the release of ctDNA fragments into the circulation.…”
Section: Challenges To Be Overcomementioning
confidence: 99%
“…Tumor size has traditionally been considered one of the determinants of prognosis in most malignancies, and hence it has been included in staging systems [ 27 , 28 ]. However, low primary tumor volume was found to be a peculiar characteristic of NB with high metastatic burden in the present study.…”
Section: Discussionmentioning
confidence: 99%